The Strengthening Sharia Economic And Financial Literacy In The Framework Of Family Economic Independence In The Post-Pandemi Covid 19 - Haryanto, Rudy; Hakim, Lukmanul; Hamim Sultoni, Mohammad (LPPM Universitas Yudharta Pasuruan, 2023)
Community service with the focus of this program on strengthening Islamic economic and financial literacy in the context of family economic independence during this pandemic is something that is right on target for the Pakong Village community, considering that many people still do not fully understand Islamic economics and finance. In addition, to increase business activity in ways that are blessed by Allah SWT, namely doing business on the basis of Islamic economic and financial literacy. This service uses teaching or lecture methods & the Asset Based Community Development method (ABCD). This method has the intention of providing guidance and assistance to participants in terms of strengthening economic literacy and sharia finance, especially to participants who already have a strong desire to start a business, and also more assistance to participants who already have an ongoing business. With regard to the sharia economy, the people of Pakong Village are very enthusiastic about understanding the contract, starting a business and marketing strategy, as well as the Islamic way of doing business. Meanwhile, with regard to Islamic finance, it is more focused on how to find solutions for finding capital in business and strategies for managing finances well.